Handbook of Behavioral Interventions in Schools 2019
DOI: 10.1093/med-psych/9780190843229.003.0011
|View full text |Cite
|
Sign up to set email alerts
|

Group Contingencies

Abstract: Group contingencies describe interventions in which a reward is delivered to a group of individuals based on meeting a predetermined target level of performance. Group contingencies have repeatedly been found to be effective in modifying student behavior. Not only are group contingences effective, but they also have several logistical advantages over individual contingencies. Namely, the delivery of a common consequence to a group of individuals increases efficiency, the use of peers as change agents increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Group contingencies are effective and efficient strategies for teachers to implement, especially because they can simultaneously affect the behavior of multiple students at a time (Maggin et al, 2012). There are three types of group contingencies: (a) independent; in which consequences are based on the outcome of students' individual behavior; (b) dependent; in which group consequences are based on the behavior of one member of the group or a small subgroup; and (c) interdependent; in which consequences are based on the behavior of the group as a whole or all group members meeting a specified criterion (Collins et al, 2019). A number of recent reviews and meta-analyses have demonstrated the near universal appropriateness and effectiveness of group contingencies across a variety of contexts and populations (e.g., Little et al, 2015;Maggin et al, 2012Maggin et al, , 2017.…”
Section: Group Contingenciesmentioning
confidence: 99%
See 4 more Smart Citations
“…Group contingencies are effective and efficient strategies for teachers to implement, especially because they can simultaneously affect the behavior of multiple students at a time (Maggin et al, 2012). There are three types of group contingencies: (a) independent; in which consequences are based on the outcome of students' individual behavior; (b) dependent; in which group consequences are based on the behavior of one member of the group or a small subgroup; and (c) interdependent; in which consequences are based on the behavior of the group as a whole or all group members meeting a specified criterion (Collins et al, 2019). A number of recent reviews and meta-analyses have demonstrated the near universal appropriateness and effectiveness of group contingencies across a variety of contexts and populations (e.g., Little et al, 2015;Maggin et al, 2012Maggin et al, , 2017.…”
Section: Group Contingenciesmentioning
confidence: 99%
“…Research comparing the effectiveness of the various types of group contingencies has failed to consistently identify one type of contingency as superior (Groves & Austin, 2017; Theodore et al, 2004). Given that each type of contingency can be effective, decisions about which type of group contingency to implement should be made based on the context of the setting, with input from individuals responsible for implementation to promote adherence (Collins et al, 2019; Ennis et al, 2016; Trevino-Maack et al, 2015). Each type of group contingency has strengths and limitations associated with it, and these should be carefully considered during intervention planning (Collins et al, 2019; Little et al, 2015).…”
Section: Selecting Group Contingenciesmentioning
confidence: 99%
See 3 more Smart Citations